Ameliorative effects of Lactobacillus fermentum isolated from individuals following vegan, omnivorous and high-meat diets on ulcerative colitis in mice - Qingsong Zhang; Wei Xiao; Leilei Yu; Fengwei Tian; Jianxin Zhao; Hao Zhang; Wei Chen; Qixiao Zhai (Food Science and Human Wellness, 2024)
Lactobacillus spp. can be beneficial for the prevention or treatment of ulcerative colitis (UC). In this study, 153 participants who followed vegan, omnivorous, or high-meat diet were recruited. Compositional analysis of the Lactobacillus community in feces revealed that Lactobacillus fermentum strains were significantly affected by diet. Administration of mixed L. fermentum strains from vegans significantly improved inflammation compared to that from omnivores and high-meat consumers, as evidenced by a significant reduction in colonic tissue damage, improvement in inflammatory cytokines, enhanced expression of ZO-1, occludin, and claudin-3, and a significant increase in short chain fatty acids concentration. The effect of a single strain of L. fermentum was similar to that of a mixed strains of L. fermentum group. Genomic analysis suggested that L. fermentum strains from the guts of vegans possessed a higher prevalence of genes involved in carbohydrate catabolism than those from the guts of omnivores and high-meat eaters. In particular, the ME2 gene is involved in the biosynthesis of acetate, a compound considered to possess anti-inflammatory properties. In conclusion, this study indicates strain-specific differences in the ability of L. fermentum strains to alleviate UC in mice, influenced by habitual diets.